Synthesis and Some Quantum Chemistry Study of Symmetrical Schiff-base Containing Dithio Group - SHEIKHSHOAIE, IRAN (Asian Journal of Chemistry, 2010)
The reaction between bis-(2-aminophenyl) disulfide and 4-phenyl azo salicylaldehyde yields a symmetrical Schiff-base N,N´-[dithio bis-(ortho-phenylene) bis-(4-azophenyl) salicylaldehyde]. This compound has been characterized by spectral methods. Geometric parameters for this Schiff-base compound and its corresponding dianion has been calculated by using AM1 semi-empirical quantum mechanical method. The most stable conformer and the charge density for all coordination sites have been determined by theoretical calculations.